THE MEANING CONSTRUCTION OF PUBG MOBILE FOR FEMALE COMMUNITY BBT MERMAIDS IN PEKANBARU CITY - Putri, Nadya Dwi; ", Yasir (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2021)
Player Unknown's Battle Ground Mobile (PUBG Mobile) is a game with the battle royale genre where players play with 100 people by online at once. The competition in this game is not only in demand by men, even women also compete in this game. In Pekanbaru City itself there is a community consisting of female PUBG Mobile players who want to prove that women can also compete even though they have to give up their stigma as women. This study aims to determine the motives, meanings, and communication experiences of female PUBG Mobile game players in Pekanbaru City.This research uses qualitative research methods with a phenomenological approach. Data collection techniques consisted of in-depth interviews, observation and documentation. The collection of informants in this study used the purposive technique with 4 informants who is female that playing game PUBG Mobile in Pekanbaru City. Data analysis techniques obtained using data collection, data reduction, data display, and decision making and verification.The results of this study indicate that the motive for using the PUBG Mobile game is divided into two, namely because of the motive which consists of hobbies, trends and environmental influences. Meanwhile, in order to motive consists of popularity and is not seen as weak. Then, the meaning of the PUBG Mobile game is the game as a medium of communication and building relationships and games as a world. For communication experience is divided into pleasant communication experiences (positive) which consists of adding friends and being more competitive. Furthermore, the experience of unpleasant (negative) communication consists of being belittled and considered rude as immoral. Keyword: Construction Meaning, PUBG Mobile, Female Community